2009
DOI: 10.1161/circulationaha.109.865956
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Cardiac Remodeling After Myocardial Infarction Are Critically Dependent on the Host Innate Immune Interleukin-1 Receptor-Associated Kinase-4 Signaling

Abstract: Background— The innate immune system greatly contributes to the inflammatory process after myocardial infarction (MI). Interleukin-1 receptor-associated kinase-4 (IRAK-4), downstream of Toll/interleukin-1 receptor signaling, has an essential role in regulating the innate immune response. The present study was designed to determine the mechanism by which IRAK-4 is responsible for the cardiac inflammatory process, which consequently affects left ventricular remodeling after MI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 34 publications
2
33
0
1
Order By: Relevance
“…6,16,17 In fact, IRAK4 contributes to TLR2-and TLR4-triggered inflammation in a mouse model of myocardial infarction. 18,19 In the present study, we demonstrate that loss of IRAK4 protects from myocarditis. Despite drastic reduction of TLR-mediated inflammation in the absence of IRAK4, antiviral pathways were markedly activated.…”
Section: Clinical Perspective On P 1554supporting
confidence: 62%
“…6,16,17 In fact, IRAK4 contributes to TLR2-and TLR4-triggered inflammation in a mouse model of myocardial infarction. 18,19 In the present study, we demonstrate that loss of IRAK4 protects from myocarditis. Despite drastic reduction of TLR-mediated inflammation in the absence of IRAK4, antiviral pathways were markedly activated.…”
Section: Clinical Perspective On P 1554supporting
confidence: 62%
“…Reperfusion is associated with additional tissue damages, called lethal reperfusion injuries (6,7). There is increasing evidence advocating the implication of innate immune cells, especially dendritic cells (DCs), in myocardial I/R injuries (8)(9)(10). DCs express a large array of DAMP receptors, particularly P2Rs that are crucial factors of the DAMP-mediated immune response (11,12).…”
mentioning
confidence: 99%
“…Besides their ability to activate T cells, DCs have been shown to orchestrate both innate and adaptive immune responses in the presence of danger signals (14,15). Some studies highlighted the important and intricate role of DCs in myocardial post-I/R injuries through the control of immune cell homeostasis (9,16). The authors suggested that DCs might be either beneficial or deleterious to organ functions according to the signaling pathways involved.…”
mentioning
confidence: 99%
“…With the development of genetically targeted animals, mouse models of myocardial infarction have become valuable tools for dissecting the cellular and molecular pathways involved in cardiac remodeling (Jones and Lefer 2000;Hoit 2001;Maekawa et al 2009;Schellings et al 2009). Investigators have used a variety of methodological approaches, such as echocardiography (Pollick et al 1995;Takagawa et al 2007;Zhang et al 2007;Scherrer-Crosbie and Thibault 2008), quantitative morphometry (Huebener et al 2008), invasive hemodynamic monitoring (ScherrerCrosbie et al 2001) and magnetic resonance imaging (Nahrendorf et al 2008), to quantitatively assess remodelingassociated parameters and to study the role of specific molecular pathways in chamber dilation, hypertrophy, and systolic and diastolic dysfunction following myocardial infarction.…”
mentioning
confidence: 99%